PENGARUH TINGKAT PERTUMBUHAN PENJUALAN, PERPUTARAN PIUTANG, DAN EFISIENSI MODAL KERJA TERHADAP RASIO LIKUIDITAS PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI PADA TAHUN 2020-2024 - Maisyarah; Ardi Hirmansah; Rina Malahayati (SUAN PUBLISHER, 2026)
Manufacturing companies are a key industrial sector in Indonesia, and national industrial development can be measured by product quality and overall company performance. Investors typically choose the manufacturing industry as their analysis object because it is one of the main sectors on the Indonesia Stock Exchange (IDX), reflecting the state of the capital market. The purpose of this study is to determine and analyze the effect of Sales Growth and Accounts Receivable Turnover on Liquidity Ratios in Consumer Goods Industry Companies in 2020-2024. The type of data used in this study is quantitative data, with secondary data sources, namely company financial reports. The collected data was analyzed using SPSS software, consisting of descriptive statistical tests, classical assumption tests, multiple linear regression, simultaneous and partial hypothesis tests, and coefficients of determination. The results showed that sales growth partially had a positive and significant effect on the Liquidity Ratio. Accounts Receivable Turnover partially had a positive and significant effect on the Liquidity Ratio. Working Capital Efficiency partially had a negative and insignificant effect on the Liquidity Ratio. Sales Growth, Accounts Receivable Turnover, and Working Capital Efficiency simultaneously had a positive and significant effect on the Liquidity Ratio in the Consumer Goods Industry Sector from 2020 to 2024. The Adjusted R2 coefficient of determination was 21.5%, while the remaining 78.5% was accounted for by variations in other variables not explained in this study, such as accounts payable, inventory, etc.